CYP1B1 and MYOC Gene Analysis of Patients with Primary Congenital Glaucoma in the Cukurova Region of Türkiye - Akbas, Ahsen Cavusoglu; Erdem, Elif; Bozdogan, Sevcan Tug; Harbiyeli, Ibrahim Inan; Yagmur, Meltem (Journal of Pediatric Genetics, 2023)
The aim of this study was to investigate the CYP1B1 and MYOC genes in patients with primary congenital glaucoma (PCG) from the Cukurova region (located in the south of Türkiye) and reveal the relationship between gene mutations and clinical severity of the disease. Molecular genetic and clinical study was conducted in 42 eyes of 26 patients who were followed for a diagnosis of PCG. The clinical diagnosis was concluded by ophthalmological examination under general anesthesia or slit-lamp biomicroscopy, gonioscopy, and measurement of the intraocular pressure. A CYP1B1 gene mutation was detected in 12 patients (46.2%). Two of these patients had a combination of CYP1B1 and MYOC mutations. The most common pathogenic variant, c.1405C > T (p.R469W) (n = 5), was present in patients with mutations, and the prognosis was poor compared with other modifications (p = 0.014). The second most common variant was c.3987G > A (p.G61E) (n = 3), which was associated with a good prognosis. The incidence of buphthalmos and the mean horizontal corneal diameter were higher in patients with mutations in the CYP1B1 and MYOC genes. All parents were found to be carriers of the mutation gene. This is the report on molecular genetic analysis of PCG in the southern region of Türkiye. Some specific genetic variants may have an effect on the prognosis of the disease. However, patients without mutations in these case groups may have mutations in genes yet to be identified.
Keywords: CYP1B1; MYOC; pathogenic variant; primary congenital glaucoma